(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Infertility has emerged as a significant disorder, primarily influenced by the stresses of the modern world, insufficient consumption of wholesome organic foods, and the evolving lifestyle patterns. Anovulation-related infertility has become a major concern among individuals of reproductive age in the current generation, largely due to unfavourable lifestyle shifts. A notable portion of couples seeking help at fertility clinics grapple with infertility caused by the absence of ovulation. In a remarkable 90% of these cases, Polycystic Ovary Syndrome (PCOS) stands as the predominant culprit. The timeless wisdom of ancient Ayurvedic scholar Sushruta continues to hold relevance today. His delineation of the four crucial factors for conception remains as imperative as it was in the past. Among these factors, the health of the ovum stands out, and disruptions in Vata Dosha often manifest as issues in ovulatory function. This narrative presents a case study involving an infertile couple who had been unable to conceive for three years. The wife’s diagnosis indicated Polycystic Ovarian Disease (PCOD). Despite undergoing conventional treatments, including hormonal therapy, their attempts were unsuccessful. The treatment strategy employed an approach called Uttar Basti alongside Prajasthapak Ghrita and Garbhaprada Yoga (a formulation supporting conception) administered orally. Notably, the outcome of this Ayurvedic intervention was the successful conception of the patient within just three months of treatment.